Effect of volumetric heat capacity of chill material on the hardness and thermal diffusivity of Al6061-quartz composite. (2020) - Hiremath, Anupama
Abstract: The paper presents the effect of volumetric heat capacity of different chill material on the hardness and thermal diffusivity of the Al6061-quartz composites. The composites are cast via liquid processing route in a sand mold consisting of end chills of different volumetric heat capacity. The Al6061 alloy ingots are initially melted in an electric furnace followed by the addition of different weight percent of quartz reinforcement. The reinforcement is varied in three steps ranging from 5 to 15 wt%, with an increment of 5 wt% at each step. The uniform dispersion of the reinforcement is brought about through the aid of a stirrer rotating at 500 rpm. Copper, mild steel, graphite and silicon carbide end chills of dimensions of 150x25x25 mm are selected and placed in the sand mold cavity into which the melt consisting of Al6061 and quartz is poured. Tests to find the hardness and thermal diffusivity are done on specimens that are drawn near the chill end to evaluate the effect of different volumetric heat capacity associated with chills of different materials. The results indicate that the chilling effect improves the quality of the chill resulting in a denser castings and this chilling effect is directly proportional to the volumetric heat capacity of the selected chill material.